Face Recognition untuk Smart Door Lock menggunakan Metode Haar-Cascades Classifier dan LBPH - Kurniasari, Arvita Agus; Sudirman, Muhammad Farizul Imami; Ramadan, Asif Mahardhika; Firmansyah, Firdaus; Damayanti, Nur Hakiki (Institut Teknologi Dirgantara Adisutjipto, 2023)
A home security system is one of the features that every homeowner must own and contemplate if they want their residence to be secure from theft and other unwanted security disturbances. Therefore, we require a support system that can enhance domestic security. In this research, the constructed system uses faces as security information. This system captures facial images using an ESP-CAM 32 board integrated with an Arduino UNO. As the system's output, this system will employ the Selenoid DoorLock and Relay features. This system detects faces using the Haar-Cascade Classifier and recognizes faces using the Local Binary Pattern Histogram (LBPH). Implementation of the method for obtaining results, namely Smart Door Lock, can autonomously unlock the door with a presentation of greater than 85%. However, if the face detected to open the door is not the same as the registrant's face and has less than 85% of the required data, the door will not open.